THE ROLE OF RATTAN AND KETAK HOME INDUSTRY IN IMPROVING THE COMMUNITY ECONOMY IN BELEKA VILLAGE, EAST PRAYA SUB-DISTRICT, CENTRAL LOMBOK REGENCY - Maenarni, Lilis; Ro'is, Ihsan; Hidayat, Ali Akbar (Journal of Finance, Economics and Business, 2025)
This study aims to analyze the role of the rattan and ketak handicraft home industry in improving the community's economy in Beleka Village, East Praya District, Central Lombok Regency. This research uses a qualitative approach with descriptive methods. The data collection techniques used were observation, interviews and documentation. Determination in this study using purposive and snowball. The data validity method used is the triangulation method. The results of this study indicate that the home industry of rattan and Ketak handicrafts plays a role in improving the economy of the community in Beleka Village, East Praya District, Central Lombok Regency. Then the role of the rattan and ketak handicraft home industry in improving the community's economy is said to be almost running well can be seen from income, health and education.